(untitled) (Philosophy and Progress, 2021)
There has been a relatively new dimension of development discourse to analyze the role of Faith Based Organizations (FBOs) in global development. In doing so, most of the academic literatures have addressed how FBOs positively contributed to the global development over the years. In contrast, there are some criticisms against the FBOs. This article attempts to elucidate three major criticisms against the FBOs including a. sectarian service provision, b. proselytization and c. terrorist financing. This article finds a mixed result arguing that there are limitations of FBOs in the concerned cases but those limitations do not reduce the significance of the FBOs in global development. Philosophy and Progress, Vol#63-64-; No#1-2; Jan-Dec 2018 P 81-108